Opportunities for small and medium entrepreneurship (SME) for green fodder and silage marketing in small holder dairy production system in India - Ravichandran, Thanammal; Hall, Andy; Kennady, Vijayalakshmy; Blümmel, Michael (2020)
The dairy production in India is increasing in the recent times and has reached the milestone. However when the overall productivity from individual animal is considered, it is still found to be very meager. The main hindrance behind the low productivity of the animal is feed and fodder scarcity. There is a huge scarcity in the availability of green fodder, dry fodder and concentrate in the country. This issue has attracted different private sector people or entrepreneur to have a start up with a feed and fodder business. The present study is aimed to assess the feed and fodder expenditure patterns between different classes of households and to propose solutions to green fodder scarcity particularly in the lean season.